Brand management in the strategic development of the company - Chen You (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is Midea’s brand management practices. The subject of research is the development and optimization of brand management strategies to enhance Midea’s strategic development and market position. The purpose of the master's thesis is to develop theoretical and practical recommendations for improving Midea’s brand management system to strengthen its market positioning, corporate reputation, and competitive advantage. Tasks of a qualifying master's thesis include: to explore the concept, essence, and main functions of a brand; to classify brand types and analyze the main approaches to their categorization; to examine core models and strategies for brand building; to provide technical and economic characteristics of Midea; to analyze Midea’s brand communication and dissemination policies; to assess the process of creating and sustaining a strong brand at Midea; to evaluate the application of global brand management experience in Midea’s operations; to propose strategies for strengthening Midea’s branding strategies and market positioning; to address challenges in brand building and maintaining Midea’s corporate image and reputation. The research outcomes include the identification of strengths and weaknesses in Midea’s current brand management practices, as well as opportunities for improvement through the application of global best practices. The analysis highlights the importance of a strong, well-defined brand strategy in achieving long-term corporate goals and maintaining competitive advantage. The obtained results have practical implications for Midea and other companies seeking to optimize their brand management systems to enhance competitiveness and corporate value.
Scientific advisor: Denchik I., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; brand management; strategic development of the company; strategic planning; branding